Methods and approaches in forest history : report no. 3 of the IUFRO Task Force on Environmental Change (IUFRO research series ;, 2000)
This book presents edited and revised versions of 23 papers selected from those presented at a major conference on History and forest resources, held in Florence, Italy, in 1998. It also includes an introduction by the first editor. The book is a companion volume to 'Forest history: international studies on socio-economic and forest ecosystem change' (IUFRO Research Series No. 2), which is also based on papers from the conference, and published by CABI Publishing in association with IUFRO. The conference was organized by the Italian Academy of Forestry Science and IUFRO Working Group S6.07.02 on Forest History. The focus of this set of papers is the different approaches and methods adopted in the study of forest history. In particular, the interdisciplinary nature of these studies is emphasized, bringing in the different perspectives of anthropologists, botanists, ecologists, foresters, historians, geneticists and geographers. As a whole, the volume demonstrates the rich diversity of approaches and methods in forest history and the need to integrate them to give a more meaningful understanding of human-nature interactions, making forest history a more effective tool for the management of forest ecosystems. All the papers are noticed separately on the CAB ABSTRACTS database.